Main determinants of preschool education in the industrial and the bay location of Cartagena of Indias City - Mabel Escorcia Muñoz; Edilber Almanza Vásquez (Universidad del Magdalena, 2014)
The pre-school education corresponds to the education offered to the boys and to the girls with fewer ages to five years, for their integral development in the biological, cognitive, psychomotor, socio-emotional and spiritual aspects, with pedagogic and recreate socialization experiences. The children who join to first of primary the industrial locality and of the bay, present academic differences depending on the establishments where they did their pre-school one. The study was to compare the community education project in Children's Homes ICBF with the educational plan of the school officials of the Ministry of Education in the Industrial locality and bay in Cartagena de Indias. The determinants found to affect the academic development of children who enter elementary school, were the nutrition, health, emotional, social and pedagogical conditions necessary and sufficient infrastructure. Preschool education in the psychological development of the child is important and essential, the interaction of family and community, the activities within the institution, where the stimuli help shape values for their integral development.